THE CONTEXT OF THE INSTITUTIONAL FOOD SUPPLYING IN THE HEALTH OF THE BRAZILIAN WORKER - Strasburg, Virgílio José; Redin, Carla (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The assurance and access to food is a basic right internationally recognized by human rights. The Programa de Alimentação do Trabalhador (PAT) is a Brazilian program created in order to ensure an adequate food intake for workers. For these communities, the provision of food through meals is done by Food and Nutrition Units (FNU). This study reviews the existing literature addressing the analysis of menus offered by companies to employees and their health evaluation. The results of the studies investigated show qualitative aspects of the menu composition and quantitative inadequacies in relation to energy and macronutrient values available in meals. On the analysis of the aspects of the workers’ nutritional conditions, it was identified a higher prevalence of overweight in those who were served by companies linked to the PAT. The findings highlight the importance of reassessing the standard quality of the meals served so it can contribute to an adequate health state of these workers.